Anti-Inflammatory and Anti-Oxidative Effects of Danggwisusan on Macrophages - Na Young Jo (MEDrang Inc., 2018)
Background Danggwisusan is a herbal medicine which is used to treat bruises, static blood, external injuries, and somatalgia in Korean medicine. The objectives of this study were to investigate whether Danggwisusan hot aqueous extract had an inhibitory effect upon inflammatory cytokine production and oxidation. Methods Cytotoxic activity of Danggwisusan extract was examined by 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. The amount of nitric oxide produced was measured using Griess reagent. Prostaglandin E2 production was measured using an enzyme immunoassay. Inflammatory cytokines (IL-1β, IL-6 and TNF-α) were measured by an enzyme linked immunosorbent assay. The anti-oxidative effect of Danggwisusan was measured by the 1,1-Diphenyl-2-picryl hydrazyl method. The amount of polyphenol and flavonoid contents were measured by Folin and Ciocalteauea phenol reagent and aluminum nitrate. Results Danggwisusan hot aqueous extracts did not show significant toxicity at 10, 20, 50, and 100 μg/ mL. At a dose of 100 μg/mL, Danggwisusan hot aqueous extract significantly inhibited nitric oxide and PGE2 production, and significantly reduced IL-1β, IL-6 and TNF-α production. At a dose of 100 μg/mL, 1,1-Diphenyl-2-picryl hydrazyl free radical scavenging capability was over 50%. Conclusions This study showed that Danggwisusan hot aqueous extract may have anti-inflammatory and anti-oxidative effects on macrophages.